(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
With the acceleration of digital transformation and the increased dependence of commercial enterprises on intelligent systems and advanced technologies, internal auditing has become a key component of transparency and environmental sustainability. Artificial intelligence (AI) is an aid to support and effectively used in the analysis of environmental data, early identification of discrepancies in operational performance, and evaluating corporate green performance. The purpose of this study is to analyze the role of AI-supported internal auditing practices in assessing the environmental impact of commercial enterprises and to highlight how smart auditing systems help to improve the quality of environmental reporting and compliance with governance and sustainability standards. The researchers developed a deductive approach to shape the theoretical aspect via an analysis related to Arabic and international literature and an inductive approach to present real-life applications in commercial firms. Hypotheses were designed to test the relationship between internal audit effectiveness, AI engagement levels, and the accuracy of environmental impact assessment. Empirical analysis was made on Zain Iraq Telecommunications (2022-2023). showed that the use of AI in internal auditing greatly improves the standard of environmental impact assessments by allowing the analysis of operating and environmental data to be carried out accurately, the timely identification of anomalies, and improvements in the organisation’s environmental performance. The results, demonstrated that the interface between internal auditing and AI provides enhanced organisational compliance with governance and sustainability standards, supports a proactive control system that facilitates data-driven decisions, increases the level of transparency of environmental reporting—thereby enhancing stakeholder confidence and advancing the commercial enterprise’s long-term sustainability.